2008
DOI: 10.1074/jbc.m800627200
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of the Calponin Homology (CH) Domain from the Smoothelin-like 1 Protein

Abstract: The SMTNL1 protein contains a single type-2 calponin homology (CH) domain at its C terminus that shares sequence identity with the smoothelin family of smooth muscle-specific proteins. In contrast to the smoothelins, SMTNL1 does not associate with F-actin in vitro, and its specific role in smooth muscle remains unclear. In addition, the biological function of the C-terminal CH-domains found in the smoothelin proteins is also poorly understood. In this work, we have therefore determined the solution structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…Both myosin light chain kinase and myosin phosphatase are regulated by several accessory proteins, and one such protein is smoothelin-like protein 1 (SMTNL1) (9). Mouse SMTNL1 is divided into two separate domains: a unique N-terminal domain (amino acids 1-346) and a C-terminal single, type-2 calponin homology domain (amino acids 346 -459) that is helix-rich and globular in structure essential for binding tropomysin (9,10). Physiological studies in smtnl1 Ϫ/Ϫ mice indicate that the protein plays a key role in modulating the contractile activity of smooth and striated muscle and is involved in adaptation in response to exercise and pregnancy (11,12).…”
Section: Smtnl1 Is a Bifunctional Co-regulator Of Pr-b Signaling And mentioning
confidence: 99%
“…Both myosin light chain kinase and myosin phosphatase are regulated by several accessory proteins, and one such protein is smoothelin-like protein 1 (SMTNL1) (9). Mouse SMTNL1 is divided into two separate domains: a unique N-terminal domain (amino acids 1-346) and a C-terminal single, type-2 calponin homology domain (amino acids 346 -459) that is helix-rich and globular in structure essential for binding tropomysin (9,10). Physiological studies in smtnl1 Ϫ/Ϫ mice indicate that the protein plays a key role in modulating the contractile activity of smooth and striated muscle and is involved in adaptation in response to exercise and pregnancy (11,12).…”
Section: Smtnl1 Is a Bifunctional Co-regulator Of Pr-b Signaling And mentioning
confidence: 99%
“…A potential protein effector of PP1M is smoothelin-like protein 1 (SMTNL1) (26 -28). SMTNL1 contains a calponin homology domain (CH2) at its C terminus while the remaining two-thirds of the primary sequence is entirely unique within the mammalian databases (26,29). Gene deletion studies in mice demonstrated that SMTNL1 plays a role in cGMP/cAMP-mediated adaptations to exercise involving direct modulation of contractile activity in vascular smooth muscle.…”
mentioning
confidence: 99%
“…It was expected that the phosphorylation of SMTNL1-TMB by PKA would impact the association with Ca-CaM and not with apo-CaM, since the binding of the latter was linked to an IQ-domain at the C-terminus (CBD2, amino acids 439–457 [10]). Indeed, we observed reductions in Ca-CaM-Sepharose binding for phosphorylated SMTNL1-TMB, with recovery of approximately 30% less bound material (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CaM provides signaling by association with specific binding sites in target proteins, both in its calcium-saturated (Ca-CaM) or its calcium-free (apo-CaM) form [8, 9]. We have previously reported that SMTNL1 possesses two CaM-binding sites: a classic CaM-binding domain (CBD1, amino acids 310–325) in the center of the protein as well as an IQ-motif that serves as an apo-CaM-binding site (CDB2, amino acids 439–457) located in the carboxy-terminal calponin homology domain [1012]. SMTNL1 was established as a bona fide CaM-binding protein within aortic A7r5 smooth muscle cells using the proximity ligation assay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation